Digital library perspectives: Some views / Norasiah Haji Harun - Haji Harun, Norasiah (Faculty of Information Management, 2010)
Digital library developments that have been the main agenda of the developed countries should also be the main agenda for developing countries so that the digital divide will not be too wide, thus affecting the effectiveness of global information sharing through libraries. This article focuses on the concept and development of digital libraries at all levels. Some views of the digital library perspectives are also highlighted.